DOP85 Rising depression and antidepressant use amongst inflammatory bowel disease patients. (25th January 2019) - Blackwell, J; Saxena, S; Alexakis, C; Cecil, E; Bottle, A; Petersen, I; Hotopf, M; Pollok, R
Abstract: Background: Depression and the use of antidepressant medication (ADM) has risen substantially in recent years in the general population and is thought to be more common in those with chronic conditions. Aims: To evaluate changes in depression and ADM use amongst patients with inflammatory bowel disease (IBD) compared with the general population. Methods: Using the Clinical Practice Research Datalink (CPRD), a nationally representative research database comprising 8% of the UK population, we identified cases of IBD diagnosed from 1999 to 2016. A non-IBD control group was matched 1:1 for age and sex with IBD patients. We defined prevalent depression in patients with a code for depression or depressive symptoms in that calendar year or patients receiving an ADM in that year as well as having a code for diagnostic depression or depressive symptoms previously. 1, 2 Medical record codes were used to determine ADM use, including selective serotonin reuptake inhibitors (SSRI) and tricyclic antidepressants (TCA). We used linear regression to analyse temporal trends. Results: We identified 9900 cases of ulcerative colitis, 4131 cases of Crohn's Disease and 14031 controls. Prevalence of depression in IBD patients doubled from 63 to 137 per 1000 patient-years at risk (PYAR) between 2000 and 2016 ( p < 0.001). IBD patients were significantly more likely to have depression than controls (14% vs. 10%, OR 1.43, 95% CI 1.19–1.72, p < 0.001). Prevalence of ADM use among IBD patients almost doubled between 2000 and 2016 (112 to 212 per 1000 PYAR, p < 0.001). Similar trends were seen for both SSRIs (61 to 134, p < 0.001) and TCAs (45 to 78, p < 0.001). Eighty-three per cent of amitriptyline prescriptions were for low-dose amitriptyline (≤30 mg/day). Antidepressant use has increased significantly in the IBD and general population. Conclusions: Patients with IBD are at 40% higher risk of depression compared with the general population and 1 in 5 patients are now using ADMs. Rates of depression have doubled between 2000 and 2016 and are mirrored by SSRI prescription. The rise in TCA use is largely accounted for by an increase in low-dose amitriptyline prescription, likely being used for the management of abdominal pain. Clinicians need to be vigilant to the risk of psychiatric co-morbidities amongst patients with IBD. References 1. Booth H, Khan O, Prevost AT, et al . Impact of bariatric surgery on clinical depression. Interrupted time series study with matched controls. J Affect Disord 2015;174:644–649 2. Rait G, Walters K, Griffin M, et al . Recent trends in the incidence of recorded depression in primary care. Br J Psychiatry 2009;195;520–524